2008
DOI: 10.1007/s10499-008-9197-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geographic origin, temperature and timing of broodstock collection on conditioning, spawning success and larval viability of Ruditapes decussatus (Linné, 1758)

Abstract: Culture of Ruditapes decussatus is clearly limited by the availability of seed, as this production proceeds almost exclusively from natural recruitment. Artificial spawning and larval rearing programs could provide an alternative source of spat. This study was designed to evaluate the effect of different conditioning temperatures on the broodstock maturation, spawning success and larval viability of two geographically (north and south of the Iberian Peninsula) distinct populations of European clam (R. decussat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 22 publications
2
38
1
1
Order By: Relevance
“…Larval length growth rates of R. decussatus from hatching to metamorphosis obtained in the fed treatments (ranged between 4.93 and 5.27 lm day -1 ) were similar to those reported in previous work by our team (Matias et al 2009) and also by Beiras and Albentosa (2004) and Ojea et al (2008), suggesting that both mono-specific diets used in the experiment had an adequate nutritional quality. However, significant differences were observed between the two diets in terms of length, length growth rates and organic matter growth rate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Larval length growth rates of R. decussatus from hatching to metamorphosis obtained in the fed treatments (ranged between 4.93 and 5.27 lm day -1 ) were similar to those reported in previous work by our team (Matias et al 2009) and also by Beiras and Albentosa (2004) and Ojea et al (2008), suggesting that both mono-specific diets used in the experiment had an adequate nutritional quality. However, significant differences were observed between the two diets in terms of length, length growth rates and organic matter growth rate.…”
Section: Discussionsupporting
confidence: 86%
“…The larvae fed with C.cal presented the highest length, suggesting that larvae fed with these microalgae seem to allocate more energy to the biosynthesis of the shell, which might have affected the success of the metamorphosis (42.81% larvae with foot). However, the percentage of metamorphosed larvae for both diets was higher than those reported by Zine et al (1998), Ojea et al (2008) and Matias et al (2009). During starvation, an increase in shell length of the clam larvae was observed.…”
Section: Discussioncontrasting
confidence: 62%
“…Aquaculture and intensive harvesting of this species on natural banks occur mainly on the Iberian Peninsula, France and other Mediterranean countries (Amaral 2009). R. decussatus is the dominant aquaculture product from southern Portugal (Matias et al 2009) and one of the most important species of clams in the fisheries and extensive aquaculture system of the Galician rias. Never theless, in recent decades the natural populations have been subject to overfishing, habitat loss, eutrophication and hypoxia and have consequently experienced a dramatic decrease (Amaral 2009).…”
mentioning
confidence: 99%
“…Much research has been carried out also on broodstock conditioning (Ojea et al, 2008;Matias et al, 2009) and on diets for Venerupis decussata larvae Matias et al, 2011) and seed (Albentosa et al, 1996a(Albentosa et al, , 1996b(Albentosa et al, , 1996c(Albentosa et al, , 1997Lamela et al, 1996;Jara-Jara et al, 1997;Fernández-Reiriz et al, 1998Pérez Camacho et al, 1998Enes and Borges, 2003) in controlled conditions. Furthermore, a number of successful trials have demonstrated the feasibility of rearing this bivalve in different European countries (Walne, 1976;Breber, 1985;Pastore et al, 1996) using different culture techniques in the sea as well as in coastal lagoons (Chessa et al, 1998(Chessa et al, , 2005Pais et al, 2006b;Serdar et al, 2007).…”
Section: Rearing In Europementioning
confidence: 99%